Responsible food marketing and standardisation: an exploratory study. Issue 7 (4th July 2016) - Cairns, Georgina; De Andrade, Marisa; Landon, Jane
Abstract : Purpose: – The purpose of this paper is to explore the feasibility and utility of developing an independently defined and accredited benchmark standard for responsible food marketing. To identify provisional evidence and insights on factors likely to be critical to its successful development and its capacity to strengthen the effectiveness of responsible food marketing policy. Design/methodology/approach: – Desk-based cross-policy domain case study. Findings: – There is promising evidence that the development and deployment of an evidence-based, independently defined and verified responsible food marketing standard is feasible. Provisional findings on factors critical to the development of an effective standard and strategically significant evidence gaps are presented as insights in support of future food marketing policy and research planning. Research limitations/implications: – Further investigation of these preliminary findings is required. Practical implications: – The study has provisionally identified an innovative intervention with the potential to strengthen statutory, voluntary and internationally coordinated food marketing control policy approaches. Originality/value: – This is the first report of research into the potential for an independent benchmark standard to advance and strengthen responsible food marketing policy goals.